Improving Senior High School Students’ Numeracy Literacy Using Deep Learning and Interactive Digital Media - Hanna Mukaromah; Lilik Indah Sari; Netriwati; Lailatul Istiqomah; Asika Melita Sari (Jurnal Pendidikan Matematika (JPM), 2025)
This study investigated the effectiveness of integrating Deep Learning pedagogical approaches with interactive digital media to improve high school students' numeracy literacy, particularly in exponential and radical domains. This research is based on the persistent underperformance of Indonesian students in international numeracy assessments, emphasizing the urgent need to adopt learning innovations that foster deep conceptual understanding, analytical reasoning, and active student engagement. Using a quantitative methodology with a quasi-group pre-test-post-test design, this study involved 35 grade ten students from SMA Negeri 12 Bandar Lampung. Data are obtained through standardized pre- and post-test instruments, supported by analytical rubrics, that assess conceptual comprehension, application fluency, problem-solving efficiency, and strategic reasoning. Statistical analyses, including normality tests, homogeneity tests, and paired t-tests, were conducted using SPSS 26.0. The findings show a statistically significant improvement in students' numeracy literacy following the implementation of integrated Deep Learning and interactive media interventions. The mean score increased from 61.40 (pre-test) to 74.06 (post-test), with a significance level of 0.000 (<0.05), indicating a significant pedagogical effect. The results show that this integrated approach increases conceptual depth, fosters reflective and analytical thinking, and promotes ongoing student engagement. Interactive media further support learning by providing dynamic, multimodal representations that facilitate understanding of abstract mathematical constructions. The study concludes that combining Deep Learning with interactive media is an effective and transformative strategy to strengthen numeracy literacy in contemporary mathematics education. Future research should include a broader sample, a wider range of mathematical topics, and additional affective or behavioural variables, such as motivation and engagement.